The yeast mitochondrial succinylome: Implications for regulation of mitochondrial nucleoids - Frankovsky, Jan; Keresztesová, Barbora; Bellová, J; Kunová, Nina; Čanigová, Nikola; Hanakova, Katerina; Bauer, Jacob A; Ondrovičová, Gabriela; Lukáčová, Veronika; Siváková, Barbara; Zdrahal, Zbynek; Pevala, Vladimír; et al. (The Journal of biological chemistry, 2021)
Acylation modifications, such as the succinylation of lysine, are post-translational modifications and a powerful means of regulating protein activity. Some acylations occur nonenzymatically, driven by an increase in the concentration of acyl group donors. Lysine succinylation has a profound effect on the corresponding site within the protein, as it dramatically changes the charge of the residue. In eukaryotes, it predominantly affects mitochondrial proteins because the donor of succinate, succinyl-CoA, is primarily generated in the tricarboxylic acid cycle. Although numerous succinylated mitochondrial proteins have been identified in Saccharomyces cerevisiae, a more detailed characterization of the yeast mitochondrial succinylome is still lacking. Here, we performed a proteomic MS analysis of purified yeast mitochondria and detected 314 succinylated mitochondrial proteins with 1763 novel succinylation sites. The mitochondrial nucleoid, a complex of mitochondrial DNA and mitochondrial proteins, is one of the structures whose protein components are affected by succinylation. We found that Abf2p, the principal component of mitochondrial nucleoids responsible for compacting mitochondrial DNA in S. cerevisiae, can be succinylated in vivo on at least thirteen lysine residues. Abf2p succinylation in vitro inhibits its DNA-binding activity and reduces its sensitivity to digestion by the ATP-dependent ScLon protease. We conclude that changes in the metabolic state of a cell resulting in an increase in the concentration of tricarboxylic acid intermediates may affect mitochondrial functions.
Keywords: Saccharomyces cerevisiae; Saccharomyces cerevisiae - proteiny; kyselina jantarová; Succinic Acid; proteomika; Saccharomyces cerevisiae Proteins; Mitochondrial Proteins; Proteomics; Transcription Factors; DNA vazebné proteiny; transkripční faktory; Protein Processing, Post-Translational; Protease La; mitochondriální proteiny; posttranslační úpravy proteinů; DNA-Binding Proteins; proteasa La